Expanding knowledge of red stripe in northwestern Argentina. New isolates and genetic diversity analysis of Acidovorax avenae - Di Pauli, Valentina; Canseco, Myrian Ayelen; Zalazar, Nicanor Oscar; Olmos, Maximiliano Gabriel; Mieja Andrada, Claudio Nahuel; Easdale, C.; Fontana, Paola Daniela (Sociedad Internacional de Técnicos de la Caña de Azúcar (ISSCT); Sociedad Argentina de Técnicos de la Caña de Azúcar (SATCA), 2025)
Poster y resumen